The need for human management model for muslims in television industries: A step toward balancing work and religious life - Nur Kareelawati Abd. Karim; Dini Farhana Baharudin; Mohd Rosmizi Abd Rahman; Rosidayu Sabran; Muhammad Khairi Mahyuddin; Othman, Khatijah Binti (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA